Exchange Rate Policy and Liability Dollarization : An Empirical Study - Berkmen, Pelin (IMF Working Papers; Working Paper ;, 2007)
The paper identifies the contemporaneous relationship between exchange rate policy and liability dollarization using three different definitions of dollarization. The presence of endogeneity makes the empirical identification elusive. We use identification through heteroskedasticity to solve the endogeneity problem in the present context (Rigobon, 2003). While we find that countries with high liability dollarization (external, public, or financial) tend to be more actively involved in exchange rate stabilization operations, we do not find evidence that floating, by itself, promotes de-dollarization.